New directions in Japan's security : non-U.S. centric evolution - Midford, Paul; Vosse, Wilhelm (Nissan Institute/Routledge Japanese Studies, 2022)
"While the US-Japan alliance has strengthened since the end of the Cold War Japan has, almost unnoticed, been building security ties with other partners, in the process reducing the centrality of the US in Japan's security; this book explains why this is happening. Japan pursued security isolationism during the Cold War, but the US was the exception. Japan hosted US bases and held joint military exercises even while shunning contacts with other militaries. Japan also made an exception to its weapons export ban to allow exports to the US. Yet, since the end of the Cold War Japan's security has undergone a quiet transformation moving away from a singular focus on the US as its sole security partner. Tokyo has begun diversifying its security ties. This text highlights this diversification. The country has initiated security dialogues with Asian neighbours, assumed a leadership role in promoting regional multilateral security cooperation and begun building bilateral security ties with a range of partners, from Australia and India to the European Union. Japan has even lifted its ban on weapons exports co-development with non-US partners. This edited collection explores this trend of decreasing centrality alongside the continued, and perhaps even growing, security (inter)dependence with the US. New Directions in Japan's Security is an essential resource for scholars focused on matters of Japan's national security. It will also interest on a wider basis those wishing to understand why Japan is developing non-American directions in its security strategy"--